The Molecular Detection of Toxoplasma Gondii Infection and its Impact on Leptin and Ferritin Levels in Diabetic Females (The Review of Diabetic Studies, 2025)
Background and Objective:Toxoplasma gondii is a widely distributed parasite infection that presents an increased risk to immunocompromised persons, particularly those with diabetes mellitus. Recent research indicates a possible link between chronic Toxoplasmosis and metabolic abnormalities in individuals with diabetes. This study sought to ascertain the incidence of Toxoplasma gondii in diabetic patients and healthy controls, evaluate serum levels of ferritin and leptin, and identify the B1 gene using real-time polymerase chain reaction. Material and Method: The research was carried out at General Kirkuk Hospital in Kirkuk, Iraq. A total of 180 blood samples were obtained, comprising 130 from individuals with type 2 diabetes mellitus and 50 from healthy controls, to assess the prevalence of anti-Toxoplasmosis antibodies IgM and IgG serologically using Cobas 4 e111, as well as to detect the B1 gene molecularly via real-time polymerase chain reaction. Furthermore, the detection of glycated haemoglobin, serum leptin, and ferritin is included. Result: The overall seropositivity for anti-Toxoplasmosis IgM and IgG was 37.80% among both diabetes patients and healthy controls; however, only 13.1% tested positive for the molecular detection of the Toxoplasma gondii B1 gene. In dindividuals with diabetes,HbA1c, serum leptin, and ferritin levels were raised compared to the healthy control group, with significant p-values for these biochemical markers being less than 0.05. Conclusion: It is concluded that Toxoplasma gondii infection is more prevalent in diabetes patients than in healthy individuals. Increased levels of leptin and ferritin may correlate with Toxoplasma gondii infection and diabetes. The B1 gene serves as a sensitive marker for the molecular identification of Toxoplasma gondii, especially in immunocompromised patients.